2019
DOI: 10.4269/ajtmh.18-0833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercial Enzyme-Linked Immunosorbent Assay Kit and In-House Fasciola gigantica Cysteine Proteinases-Based Enzyme-Linked Immunosorbent Assays for Diagnosis of Human Fascioliasis

Abstract: Fascioliasis, caused by Fasciola hepatica and Fasciola gigantica infection, is a major food-borne trematodiasis in many places of the world, with the central region of Vietnam being reported as a highly endemic area. Stool examination for Fasciola eggs is not a sensitive method, and immunodiagnostic methods are preferable. We investigated various enzyme-linked immunosorbent assays (ELISAs) to evaluate their efficacy for fascioliasis diagnosis. Test sera used are primarily screened using an ELISA kit produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Comparison with other methods that can identify samples from cattle with pre-patent or early infections distinguishes antigen detection, which is undetectable by the usual parasitological tests. In addition, these assays give a more accurate indication of the current state of infections [13]. In a previous study, Attallah et al [10] identified a band at 27 kDa during E/S antigenic examinations in the adult worm of F. gigantica and the sera of humans infected with F. gigantica.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with other methods that can identify samples from cattle with pre-patent or early infections distinguishes antigen detection, which is undetectable by the usual parasitological tests. In addition, these assays give a more accurate indication of the current state of infections [13]. In a previous study, Attallah et al [10] identified a band at 27 kDa during E/S antigenic examinations in the adult worm of F. gigantica and the sera of humans infected with F. gigantica.…”
Section: Discussionmentioning
confidence: 99%
“…In the hepatic phase, serological tests like enzyme-linked immunosorbent assay (ELISA) and indirect hemagglutination (IHA) tests are expected to have a high diagnostic yield. 3,8 But due to a lack of easy availability, both of these tests could not be used on our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to a long period of latency and a biphasic mode of presentation, early identification of fascioliasis continues to pose a diagnostic challenge. In the hepatic phase, serological tests like enzyme‐linked immunosorbent assay (ELISA) and indirect hemagglutination (IHA) tests are expected to have a high diagnostic yield 3,8 . But due to a lack of easy availability, both of these tests could not be used on our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant proteins and synthetic peptides based on cysteine proteases are used in immunodiagnostic assays (Intapan et al 2005;Tantrawatpan et al 2005;Gonzales-Santana et al 2013;Meshgi et al 2018). The cysteine protease-based ELISAs were further simplified by using cystatin-capture (CC)-ELISA to detect anti-cysteine protease antibodies without the need for a purified or recombinant cysteine protease; CC-ELISA using whole worm extract was reported suitable for practical diagnosis of fasciolosis (Ikeda 1998;Tantrawatpan et al 2005;Tran et al 2019). Pen-side diagnostic tests have been evaluated to make diagnosis easier, faster, and more cost-effective.…”
Section: Diagnostic Approaches For Human Fasciolosismentioning
confidence: 99%
“…2005; Tran et al . 2019). Pen-side diagnostic tests have been evaluated to make diagnosis easier, faster, and more cost-effective.…”
Section: Diagnostic Approaches For Human Fasciolosismentioning
confidence: 99%